Dos nuevos gecos (sauria: gekkonidae, sphaerodactylinae) para colombia: lepidoblepharis xanthostigma (noble) y descripción de una nueva especie (1983)
Lepidoblepharis xanthostigma is reported from Colombia on the basis of two specimens captured in hot climate areas of the middle Magdalena River valley in Santander. It is distinguished from other Colombian Lepidoblepharis species by several large, dark, prominent spots on a light background in the gular región, a light "W" shaped band across the back of the head, and a convex posteriorly directed margin on the mental scale instead of straight or concave as in other species of the genus. A new species which it is described, lives in temperate climate area between 1.200-2.000 meters elevation in the western and central cordilleras and is distinguished by unique scales of two different sizes on the back of adult lizards: small piramidal scales surrounded by even smaller scales about ⅛ their size.